Interleukin-16 Polymorphism Is Associated with an Increased Risk of Ischemic Stroke - Xiao-li Liu; Jian-zong Du; Yu-miao Zhou; Qin-fen Shu; Ya-guo Li (Hindawi Limited, 2013)
Clinical and experimental data have demonstrated that inflammation plays fundamental roles in the pathogenesis of ischemic stroke. Interleukin-16 (IL-16) is identified as a proinflammatory cytokine that is a key element in the ischemic cascade after cerebral ischemia. We aimed to examine the relationship between the IL-16 polymorphisms and the risk of ischemic stroke in a Chinese population. A total of 198 patients with ischemic stroke and 236 controls were genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and DNA sequencing method. We found that the rs11556218TG genotype and G allele of IL-16 were associated with significantly increased risks of ischemic stroke (TG versus TT, adjusted OR = 1.88; 95% CI, 1.15-3.07; G versus T, adjusted OR = 1.54; 95% CI, 1.05-2.27, resp.). However, there were no significant differences in the genotype and allele frequencies of IL-16 rs4778889 T/C and rs4072111 C/T polymorphisms between the two groups, even after stratification analyses by age, gender, and the presence or absence of hypertension, diabetes mellitus, hypercholesterolemia, and hypertriglyceridemia. These findings indicate that the IL-16 polymorphism may be related to the etiology of ischemic stroke in the Chinese population.